2015
DOI: 10.3126/jsan.v1i1.13584
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrathecal bupivacaine with or without fentanyl for urosurgeries

Abstract: Introduction: Spinal anaesthesia has been widely used for urological operations because it permits early recognition of symptoms caused by overhydration, transurethral resection of prostate syndrome and bladder perforation. Short acting spinal anaesthesia may help to prevent complications associated with delayed immobilization. Our study was undertaken to examine whether adding 25?g fentanyl to bupivacaine would intensify sensory and motor block without prolonging recovery time.Materials and Methods: Ninety Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(17 reference statements)
0
0
1
Order By: Relevance
“…Similarly another comparative study in India [11], showed more decreased in systolic BP in non-exposed group than study group. In contrast to the present study, comparative study conducted in Australia [16], showed there were no differences on incidence and severity of hypotension between the groups.…”
contrasting
confidence: 99%
“…Similarly another comparative study in India [11], showed more decreased in systolic BP in non-exposed group than study group. In contrast to the present study, comparative study conducted in Australia [16], showed there were no differences on incidence and severity of hypotension between the groups.…”
contrasting
confidence: 99%